ALCOHOL-RELATED PROBLEMS IN PORTUGAL: SEARCHING FOR CONNECTIONS - Lagarto, Mª Inês Pinto (American International Journal of Social Science Research, 2022)
Based on a doctoral thesis, the study investigates the relationship between alcohol consumption and social problems. The main goals were to recognize the social problems most associated with alcohol, find interconnections and understand how society looks at the problem, especially in what concerns this particular relationship. This study employs document analysis and interviews as qualitative data collection methods, using a non-probability sampling. Were analyzed public records, namely national annual reports from 6 different official organisms, regarding 2015?. Were also interviewed 62 alcoholic patients, from 5 distinct support services? The interview data were analyzed from a biographical perspective, which allowed the analysis of the parallel evolution of social problems within the history of consumption. The results of this research confirm a dynamic systemic and multidimensional relationship between alcoholism and social factors/problems, especially family, legal, and work issues. The results also reveal that society devalues and neglects this association, by not analyzing or recording alcohol consumption. The findings of this study suggest that the lack of recognition of the problem interferes in the early detection and difficult alcoholism intervention. JEL Classification Codes: I, I19, I39.